win and sin: Predicate Transformers for Concurrency - Lamport, Leslie (ACM Transactions on Programming Languages and Systems. Also appeared as SRC Research Report 17 (May 1987)., 1990)
I had long been fascinated with algorithms that, like the bakery algorithm of [12], do not assume atomicity of their individual operations. I devised the formalism first published in [33] for writing behavioral proofs of such algorithms. I had also long been a believer in invariance proofs, which required that the algorithm be represented in terms of atomic actions. An assertional proof of the bakery algorithm required modeling its nonatomic operations in terms of multiple atomic actions–as I did in [12]. However, it's easy to introduce tacit assumptions with such modeling. Indeed, sometime during the early 80s I realized that the bakery algorithm required an assumption about how a certain operation is implemented that I had never explicitly stated, and that was not apparent in any of the proofs I had written. This paper introduces a method of writing formal assertional proofs of algorithms directly in terms of their nonatomic operations. It gives a proof of the bakery algorithm that explicitly reveals the needed assumption. However, I find the method very difficult to use. With practice, perhaps one could become facile enough with it to make it practical. However, there don't seem to be enough algorithms requiring reasoning about nonatomic actions for anyone to acquire that facility.